Comment On The Paper: Design Of Merensky Reef Crush Pillar - F. S. A. de Frey (The Southern African Institute of Mining and Metallurgy, 2011)
The author would like to refer to his contribution to the paper `Design of pillar systems in South Africa' by Ozbay et al. 1. The authors agreed `wholeheartedly that further research, together with carefully planned field trials, in pursuit of this potentially highly rewarding concept' of the small span small pillar method is warranted. On 30 September 2010 the author went underground at the Kroondal Chrome Mine to observe how the concept of smaller spans was being applied. He was pleasantly surprised to find that the typical coal mine bord and pillar sytem was being used very successfully. Although the deepest mining was taking place at a depth of only 450 metres, Kroondal would be an ideal mine to do further research together with carefully planned field trials. At Crown Mines Gold Mine, where the author worked, he was informed that the first recorded rockburst took place at a depth of 635 metres below surface. The depth of the platinum and chrome mines is increasing, with the risk of an excalation in injuries and fatalities due to 'backbreaks' and siesmic activity. The rock engineer at Kroondal was not aware of backbreaks occuring on the mine. It is important that the rock engineers of the base mineral and gold mines get together and give more serious attention to the host rock environment in which the pillars are situated.